Unforgiven : a Fallen novel - Kate, Lauren (Kate, Lauren. Fallen novel., 2015)
Dark angel Cam made a bet with Lucifer: he has fifteen days to convince the only girl who really matters to him to love him again. If he succeeds, Lilith will be allowed back into the world, and they can live their lives together. But if he fails ... there's a special place in Hell just for him.